The helminth fauna of the greater horseshoe bat (Rhinolophus ferrumequinum) (Chiroptera: Rhinolophidae) on the territory of Serbia - Horvat, Žolt; Čabrilo, Borislav; Paunović, Milan; Karapandža, Branko; Jovanović, Jelena; Budinski, Ivana; Bjelić Čabrilo, Olivera (Biologia Serbica, 2016)
An analysis of the helminth fauna of the greater horseshoe bat was conducted for the first time on the territory of Serbia. The host sample consisted of 17 individuals of the greater horseshoe bat (Rhinolophus ferrumequinum) collected from 8 localities in Serbia. Fifteen individuals (88.2%) were found to be infected with helminth parasites. Five parasite species were identified: three digeneans (Plagiorchis sp., Prosthodendrium longiforme, Leci- thodendrium linstowi) and two nematodes (Strongylacantha glycirrhiza, Litomosa ottavianii). A total of 108 helminth individuals were collected from the hosts. The species S. glycirrhiza had the highest prevalence of infection (76.5%) and was represented by the highest number of individuals (65). Infection with a single parasite species was most commonly observed.